1984
DOI: 10.1056/nejm198408093110601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Theophylline on Diaphragmatic Strength and Fatigue in Patients with Chronic Obstructive Pulmonary Disease

Abstract: We studied the effects of theophylline on diaphragmatic strength and fatigue in 15 patients with severe chronic obstructive pulmonary disease. Diaphragmatic strength was assessed by measurement of the transdiaphragmatic pressure generated at functional residual capacity during a maximal inspiratory effort against closed airways. Diaphragmatic fatigue was induced by resistive loaded breathing. The electrical activity of the diaphragm was recorded with an esophageal electrode during the fatigue runs, and the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(75 citation statements)
references
References 20 publications
6
69
0
Order By: Relevance
“…Among them, dose-dependent bronchodilatation leads to improvement of ventilatory patterns and reduces trapped air. In patients with chronic obstructive pulmonary disease, theophylline was shown to improve oxygenation as well as the forced expiratory volume in one second [15,22]. Similar effects can be expected in subjects acutely exposed to hypobaric hypoxia [23].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Among them, dose-dependent bronchodilatation leads to improvement of ventilatory patterns and reduces trapped air. In patients with chronic obstructive pulmonary disease, theophylline was shown to improve oxygenation as well as the forced expiratory volume in one second [15,22]. Similar effects can be expected in subjects acutely exposed to hypobaric hypoxia [23].…”
Section: Discussionsupporting
confidence: 51%
“…The multiple pharmacological effects of theophylline (a phosphodiesterase inhibitor) are well characterized, and comprise a decrease in cerebral blood flow [8], suppression of microvascular permeability in the brain and lungs [9], a bronchodilating effect [10], central respiratory stimulation [11], a decrease in pulmonary arterial pressure [12], inhibition of inflammatory mediators [13], a reduction in periodic breathing [14], improved diaphragmatic contractility [15], and induction of mild diuresis.…”
mentioning
confidence: 99%
“…3,8,9,14 The mechanism for this is unknown, but extracellular calcium may be necessary for aminophylline to have a potentiating effect on diaphragmatic contractility. 14 In the present study, we showed that inhaled aminophylline significantly increased contractility in fatigued diaphragm (groups 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Among these drugs, aminophylline IV, a methylxanthine methyltransferase compound, has been widely used to increase contractility of fatigued diaphragm in healthy subjects 8 and in patients with chronic obstructive pulmonary disease (COPD). 9 Early studies [10][11][12] suggested the efficacy of an inhaled form of methylxanthine, but, according to a MEDLINE search (key terms: aminophylline, methylxanthine, inhalation, and diaphragmatic fatigue; years: , this modality has not been used to treat diaphragmatic fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…These are: MV modes that help the diaphragm contribute to respiration in an active way; various exercise methods, prevention of catabolic processes and pharmacotherapy [5]. Studies on both humans and animals have show that the application of prophylactic theophylline in pharmacotherapy practices prevents diaphragmatic weakness and reverses diaphragmatic fatigue [6][7][8][9][10][11][12][13][14][15][16][17]. However, in most of these studies, the effect of theophylline on the contraction strength of diaphragmatic muscles has been evaluated, but the effect on diaphragmatic atrophy was never mentioned.…”
mentioning
confidence: 99%